1993
DOI: 10.1152/ajpgi.1993.264.4.g645
|View full text |Cite
|
Sign up to set email alerts
|

The computer as referee in the analysis of human small bowel motility

Abstract: The aim of this study was to determine whether visual analysis of graphic records of small bowel motility is a reliable method of discriminating pressure events caused by bowel wall contraction from those of extraenteric origin and to compare this method with computerized analysis. Each of six independent observers was supplied with the same pair of records of 1 h of fasting diurnal duodenojejunal motility, acquired with a 3-channel ambulant data-logging system; one record included many artifacts due to body m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 0 publications
2
27
0
Order By: Relevance
“…The main reason for this restriction was poor interobserver agreement when evaluating short distance BTEs, because impedance recordings of the small bowel appear to be more affected by artifacts than in the esophagus. Similar difficulties have been encountered earlier by others [22] and by our own group [3] in the visual analysis of small bowel contractions. The restriction to MII events exceeding 10 cm in length in our present study is further substantiated by the validation study of Imam et al [12].…”
Section: Discussionsupporting
confidence: 77%
“…The main reason for this restriction was poor interobserver agreement when evaluating short distance BTEs, because impedance recordings of the small bowel appear to be more affected by artifacts than in the esophagus. Similar difficulties have been encountered earlier by others [22] and by our own group [3] in the visual analysis of small bowel contractions. The restriction to MII events exceeding 10 cm in length in our present study is further substantiated by the validation study of Imam et al [12].…”
Section: Discussionsupporting
confidence: 77%
“…A phase III was ignored if it occurred within 20 min after the start of ingestion of a drink or a meal, as conversion of interdigestive to postprandial motor pattern is not necessarily an immediate process [1,19]. A validated computer program calculated the incidence and amplitude of contractions as well as the AUC [5], Contractile activity was analyzed for the total period between the start of ingestion and the appearance of the next phase 111 and for consecutive 30-rnin intervals thereof. In one experi ment, a phase III was not seen within the 7-hour period after the liq uid meal and before the volunteer had his evening meal.…”
Section: Data Handling and Analysismentioning
confidence: 99%
“…Recently, 24-hour ambulatory manometry has become available, now allowing prolonged recordings in ambula tory subjects [3,4], Furthermore different groups have developed dedicated computer softwares so that small bowel motor activity can be analyzed in greater detail [5][6][7][8], These new techniques now enable us to study the phys iology of postprandial small bowel motility in man.…”
Section: Introductionmentioning
confidence: 99%
“…Still, visual analysis is relevant to make fine discrimination between true contractions and artefacts. Other authors have shown computer-assisted interpretation of graphic records of small bowel motility to be a reliable method of discriminating pressure events caused by bowel wall contraction from those of extra-enteric origin, which is the main confounder in the analysis (Benson et al 1993). At present, no software is available that provides a fully automated small bowel manometry analysis.…”
Section: Discussionmentioning
confidence: 99%